2015
DOI: 10.1016/j.apgeog.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Mapping eastern equine encephalitis virus risk for white-tailed deer in Michigan

Abstract: Eastern equine encephalitis (EEE) is a mosquito-borne viral disease that is often fatal to humans and horses. Some species including white-tailed deer and passerine birds can survive infection with the EEE virus (EEEV) and develop antibodies that can be detected using laboratory techniques. In this way, collected serum samples from free ranging white-tailed deer can be used to monitor the presence of the virus in ecosystems. This study developed and tested a risk index model designed to predict EEEV activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…melanura ecology and EEEV foci to develop need to be done, and changes in temperature regime favoring a longer growing season as well. These specific landforms with the observed clusters of equid and human cases add specificity and sensitivity to such predictions, beyond the more generalized wetland associations as proximal risk factors for EEE for equids and humans, such as the incomplete drainage lake type ( Davis 1931 , Ross and Kaneene 1995 ), or swamps and wetlands ( Schmitt et al 2007 , Downs et al 2015 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…melanura ecology and EEEV foci to develop need to be done, and changes in temperature regime favoring a longer growing season as well. These specific landforms with the observed clusters of equid and human cases add specificity and sensitivity to such predictions, beyond the more generalized wetland associations as proximal risk factors for EEE for equids and humans, such as the incomplete drainage lake type ( Davis 1931 , Ross and Kaneene 1995 ), or swamps and wetlands ( Schmitt et al 2007 , Downs et al 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…Human cases of EEE have been reported previously ( MMWR 1980 , 1992 ; Davenport et al 1982 ; Deresiewicz et al 1997 ; Lindsey et al 2018 ), including a review of the outbreak in 2019 when 10 human cases in Michigan were reported ( Lindsey et al 2020 ). Case reports in various animal species ( McLean et al 1985 ; MMWR 1993 , 1995 ; Williams et al 2000 ; Andrews et al 2018 ; Thompson et al 2021 ) and risk analysis of equid and white-tailed deer outbreaks ( Ross and Kaneene 1995 , 1996 ; Schmitt et al 2007 ; Downs et al 2015 ) have been published previously. Additionally, there are at least two unpublished master’s theses dealing with the topic of EEE in Michigan ( Shaw 1976 , Solis 2000 ), and an important but unpublished report of studies of mosquito and bird involvement conducted from 1980 to 1982 ( Newson 1983 ).…”
mentioning
confidence: 99%